Simultaneous amperometric aptasensor based on diazonium grafted screen-printed carbon electrode for detection of CFP10 and MPT64 biomarkers for early tuberculosis diagnosis - Yunus, Muhammad Hafiznur; Yusof, Nor Azah; Abdullah, Jaafar; Sulaiman, Yusran; Ahmad Raston, Nurul Hanun; Md Noor, Siti Suraiya (Multidisciplinary Digital Publishing Institute, 2022)
Early diagnosis is highly crucial for life-saving and transmission management of tuberculosis (TB). Despite the low sensitivity and time-consuming issues, TB antigen detection still relies on conventional smear microscopy and culture techniques. To address this limitation, we report the development of the first amperometric dual aptasensor for the simultaneous detection of Mycobacterium tuberculosis secreted antigens CFP10 and MPT64 for better diagnosis and control of TB. The developed sensor was based on the aptamers–antibodies sandwich assay and detected by chronoamperometry through the electrocatalytic reaction between peroxidase-conjugated antibodies, H2O2, and hydroquinone. The CFP10 and MPT64 aptamers were immobilized via carbodiimide covalent chemistry over the disposable dual screen-printed carbon electrodes modified with a 4-carboxyphenyl diazonium salt. Under optimized conditions, the aptasensor achieved a detection limit of 1.68 ng mL−1 and 1.82 ng mL−1 for CFP10 and MPT64 antigens, respectively. The developed assay requires a small sample amount (5 µL) and can be easily performed within 2.5 h. Finally, the dual aptasensor was successfully applied to clinical sputum samples with the obtained diagnostic sensitivity (n = 24) and specificity (n = 13) of 100%, respectively, suggesting the readiness of the developed assay to be used for TB clinical application.